Mapurbe Identity and Admapu in David Aniñir's Poetry. - ECHEVERRÍA, ANDREA (Bulletin of Latin American Research, 2019)
This article proposes a reading of David Aniñir's poetry that examines how he resignifies elements pertaining to admapu or Mapuche norms and practices in the metropolis. Aniñir is an urban Mapuche poet who lives in Santiago, Chile and displays interest in recovering his roots. While he defies preconceptions about indigenous peoples in his poetry, he includes Mapuche culture in his depiction of mapurbe identity. In his writing, Aniñir incorporates Mapuche key concepts and social roles such as yeyipun (prayer), pewma (dreams), werken (messenger), ngenpin (ritual speaker) and machi (spiritual authority and shaman), giving them new meanings within the urban context.